Perkawinan Beda Agama Menurut Hukum Positif, Hukum Islam dan Hak Asasi Manusia di Indonesia - Yunike Rahma Hermanto (Universitas Sebelas Maret, 2024)
Problems regarding marriage are becoming increasingly complex along with the development of Indonesian society. There are marriage cases that are worth debating because marriage is a legal action that has consequences for the married couple and the country where they live. One of them is interfaith marriage, which has become a current phenomenon. This kind of study is known as doctrinal or normative legal research. In addition to primary, secondary, and tertiary legal materials, this research will make use of secondary legal sources. The laws pertaining to interfaith weddings have been examined from a legal and human rights standpoint in order to conduct study into the fundamentals and systematics of law. The regulations in the marriage law do not clearly regulate interfaith marriages and do not explicitly state that interfaith marriages are prohibited. Customary law also does not provide an explicit explanation regarding interfaith marriages, there are customary laws that do not recognize interfaith marriages, and there are also customary laws that recognize them using several methods of recognition for orderly administration. However, in the Islamic context, interfaith marriages are considered absolutely haram and have the potential to cause controversy and disharmony in the household. Restrictions created by law regarding interfaith marriages do not violate human rights. Of course, if the law is made in accordance with morals, values, public order, security, and religious, it will not be considered a violation of human rights. Even though the Marriage Law and laws in Indonesia do not explicitly regulate interfaith marriages, in practice, people tend to follow existing religious and cultural norms, with the view that marriages should be between individuals who have the same religious beliefs.